2019
DOI: 10.1186/s12870-019-1850-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis based on a combination of sequencing platforms provides insights into leaf pigmentation in Acer rubrum

Abstract: Background Red maple ( Acer rubrum L.) is one of the most common and widespread trees with colorful leaves. We found a mutant with red, yellow, and green leaf phenotypes in different branches, which provided ideal materials with the same genetic relationship, and little interference from the environment, for the study of complex metabolic networks that underly variations in the coloration of leaves. We applied a combination of NGS and SMRT sequencing to various red maple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 101 publications
3
37
0
Order By: Relevance
“…Especially in autumn, when the leaf color of the autumn leaf tree changes, which attracts people's attention. In order to increase the ornamental effect of a garden, colorful leaf tree species are widely used in gardens, such as red maple (Acer rubrum L.) of red leaves [1], gingko (Ginkgo biloba L.) of yellow leaves [2], etc. The direct cause of leaf discoloration is the change in contents of chlorophyll, carotenoids, anthocyanins and other pigmented substances, which are affected by both inheritance and environmental factors, and are regulated by leaf cell microstructure and metabolism [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in autumn, when the leaf color of the autumn leaf tree changes, which attracts people's attention. In order to increase the ornamental effect of a garden, colorful leaf tree species are widely used in gardens, such as red maple (Acer rubrum L.) of red leaves [1], gingko (Ginkgo biloba L.) of yellow leaves [2], etc. The direct cause of leaf discoloration is the change in contents of chlorophyll, carotenoids, anthocyanins and other pigmented substances, which are affected by both inheritance and environmental factors, and are regulated by leaf cell microstructure and metabolism [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the research focuses on red leaf discoloration. For example, Chen et al [1] found that the accumulation of cyanidin and reduction of chlorophyll and carotenoids produced the redness of red maple leaves. Gu et al [6] found that the anthocyanin content of the leaves of Prunus cerasifera increased under light induction, and the leaves gradually turned purple.…”
Section: Introductionmentioning
confidence: 99%
“…At present, transcriptome sequencing technology has been used to study vegetables color formation [28], ower color mechanisms [10,29], fruit development [30,31]. Some scholars have analyzed the color mechanism of the related species in Acer [32]. However, due to the lack of genomic reference sequences, the molecular mechanism of leaf color is di cult to decipher in A. pseudosieboldianum.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing analyses were assessed as previously described [44]. A combination of nextgeneration sequencing (NGS) and single-molecule real-time (SMRT) sequencing were adopted for this study.…”
Section: Rna Sequencing Experimentsmentioning
confidence: 99%
“…Leaf senescence is the last stage in the life history of red maple leaves, from maturation tosenescence, where the most obvious external change is yellowing. Our previous research revealed that the yellowing of the senescing leaves of red maple is primarily attributed to the degradation of chlorophyll, not the emergence of yellow plant-based pigments such as carotenoids [45]. We used ultrahigh-performance liquid chromatograph Q extractive mass spectrometry (UHPLC-QE-MS) to analyze the metabolism of nonsenescing leaves (fully expanded non-senescing leaves) and senescing leaves (100% yellowing of the leaf surface; ~95% chlorophyll loss) (Fig.…”
Section: Leaf Senescencementioning
confidence: 99%